Hydroxyalkylation/alkylation of furfural and 2-methylfuran over functionalized SBA-15: tuning acidity and hydrophobicity for SAF precursor production - Juan Manuel Gimenez; Lucas Gabriel Tonutti; Claudia Amelia Neyertz; Cristián Alejandro Ferretti; Carlos Alberto Querini; María Soledad Zanuttini (Fuel, 2026)

Extreme temperatures and non-work at work - Ignacio Belloc; José Ignacio Gimenez-Nadal; José Alberto Molina (Economics & Human Biology, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

Cell Cycle Dysfunction and Metabolic Alterations Consistent With Pathological Tau in Progressive Supranuclear Palsy Derived Fibroblasts - Roberta De Mori; Francesca Ciaiola; Valentina Nesci; Juliette Gimenez; Marco de Bardi; Luisa Pieroni; Susanna de Stefano; Giovanna Borsellino; Cristiana Valle; Alberto Ferri; Alessandro Stefani; Davide Mascioli; et al. (Molecular Neurobiology, 2026)

Multienzymatic extracts from fishery waste alter digestive metabolism and intestinal microbiota in red claw crayfish across ontogeny - Emily S. García Martínez; Pau Germino Swinyard; Ariadna G. Battista; Gonzalo Coccolo; Valentín Villamonte; Alberto Peña-Rodríguez; Analía V. Fernández-Gimenez; Laura Susana López Greco (Aquaculture International, 2025)

Imagine, Discover, Inspire: Proceedings of the 4th International Conference of the Trisomy 21 Research Society - Lisi Flores-Aguilar; Eric D. Hamlett; Paula Araya; Eugenio Barone; Anita Bhattacharyya; Maria Carmona-Iragui; Li Chan; Brad Christian; Alberto C. S. Costa; Floriana Costanzo; Laura Del Hoyo Soriano; Mara Dierssen; et al. (NeuroMolecular Medicine, 2025)
Down syndrome (DS) or trisomy 21 (T21) is present in a significant number of children and adults around the world and is associated with cognitive and medical challenges. Through research, the T21 Research Society (T21RS), established in 2014, unites a worldwide community dedicated to understanding the impact of T21 on biological systems and improving the quality of life of people with DS across the lifespan. T21RS hosts an international conference every two years to support collaboration, dissemination, and information sharing for this goal. In 2022, T21RS hosted an international conference in Long Beach, California, from June 9 to 12. The conference, attended by 483 people including scientists, families, self-advocates, and industry representatives from 17 countries, was a dynamic and interactive meeting that shared discoveries from international research teams. This summary highlights the scientific discoveries shared at the 4th T21RS meeting with the Imagine, Discover, Inspire theme.

The gasoline price and the commuting behavior of US commuters: Exploring changes to green travel mode choices - Ignacio Belloc; José Ignacio Gimenez-Nadal; José Alberto Molina (Journal of Transport Geography, 2024)

Effect of prenatal exposure to organophosphates and pyrethroid pesticides on neonatal anthropometric measures and gestational age - María José Gimenez-Asensio; Antonio F. Hernandez; Desire Romero-Molina; Beatriz Gonzalez-Alzaga; Octavio P. Luzardo; Luis Alberto Henríquez-Hernández; Luis D. Boada; Helena García-Cortés; Inmaculada Lopez-Flores; María Dolores Sanchez-Piedra; Clemente Aguilar-Garduño; Marina Lacasaña (Environmental Research, 2023)

Antiparasitic activity of two Brazilian plants: Eugenia mattosii and Marlierea eugeniopsoides - Giovana Vechi; Adrielli Tenfen; Efrain Salamanca Capusiri; Alberto Gimenez; Valdir Cechinel-Filho (Natural Product Research, 2021)

Functional and in silico assessment of MAX variants of unknown significance - Iñaki Comino-Méndez; Luis J Leandro-García; Guillermo Montoya; Lucía Inglada-Pérez; Aguirre A. de Cubas; María Currás-Freixes; Carolyn Tysoe; Louise Izatt; Rocío Letón; Álvaro Gómez-Graña; Veronika Mancikova; María Apellániz-Ruiz; et al. (Journal of Molecular Medicine, 2015)

The living library of The Cotapata National Park in Bolivia: an example of application of Bolivian law on the access to genetic resources - Lucia Acebey; Amira Apaza; Rosy de Michel; Stephan Beck; Valérie Jullian; Grace Ruiz; Alberto Gimenez; Séverine Chevalley; Michel Sauvain (Biodiversity and Conservation, 2008)